Can Russia compete? - Desai, Raj M., 1966-; Goldberg, Itzhak, 1947- (World Bank e-Library., 2008)
"Looks at Russian government's push toward a knowledge-based economy, particularly in the manufacturing sector. Quantifies and benchmarks sector's relative strengths, identifying opportunities to increase Russian productivity and competitiveness. Examines underlying firm-level determinants of knowledge absorption, competitiveness, and productivity, with an eye to improving workers' skill levels and the investment climate"--Provided by publisher